Synthesis and Antitubercular Activity of Heteroaromatic Isonicotinoyl and 7-Chloro-4-Quinolinyl Hydrazone Derivatives. (2010) - Ferreira, Marcelle de L.; Gonçalves, Raoni S.B.; Cardoso, Laura N. de F.; Kaiser, Carlos R.; Candéa, Andre L.P.; Henriques, Maria das Graças M. de O.; Lourenço, Maria C.S.; Bezerra, Flávio A.F.M.; de Souza, Marcus V. N.
Abstract : Two series of N' (E)-heteroaromatic-isonicotinohydrazide derivatives (3a-f and 4a-b) and 1-(7-chloroquinolin-4-yl)-2-[(heteroaromatic)methylene]hydrazone derivatives (5a-f and 6a-b) have been synthesized and evaluated for their in vitro antibacterial activity against Mycobacterium tuberculosis H37 Rv. Several compounds were noncytotoxic and exhibited significant minimum inhibitory concentration (MIC) activity (3.12, 2.50, 1.25, or 0.60 μg/mL), which can be compared to that of the first-line drugs ethambutol (3.12 μg/mL) and rifampicin (2.0 μg/ml). These results can be considered an important starting point for the rational design of new leads for anti-TB compounds.